The structure-selective endonucleases GEN1 and MUS81 mediate complementary functions in safeguarding the genome of proliferating B lymphocytes - Keith Conrad Fernandez; Laura Feeney; Ryan M Smolkin; Wei-Feng Yen; Allysia J Matthews; William Alread; John HJ Petrini; Jayanta Chaudhuri (eLife)
During the development of humoral immunity, activated B lymphocytes undergo vigorous proliferative, transcriptional, metabolic, and DNA remodeling activities; hence, their genomes are constantly exposed to an onslaught of genotoxic agents and processes. Branched DNA intermediates generated during replication and recombinational repair pose genomic threats if left unresolved, and so they must be eliminated by structure-selective endonucleases to preserve the integrity of these DNA transactions for the faithful duplication and propagation of genetic information. To investigate the role of two such enzymes, GEN1 and MUS81, in B cell biology, we established B-cell conditional knockout mouse models and found that deletion of GEN1 and MUS81 in early B-cell precursors abrogates the development and maturation of B-lineage cells while the loss of these enzymes in mature B cells inhibits the generation of robust germinal centers. Upon activation, these double-null mature B lymphocytes fail to proliferate and survive while exhibiting transcriptional signatures of p53 signaling, apoptosis, and type I interferon response. Metaphase spreads of these endonuclease-deficient cells show severe and diverse chromosomal abnormalities, including a preponderance of chromosome breaks, consistent with a defect in resolving recombination intermediates. These observations underscore the pivotal roles of GEN1 and MUS81 in safeguarding the genome to ensure the proper development and proliferation of B lymphocytes.